2021
DOI: 10.1093/g3journal/jkab086
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-conserved sequences in the genomes of highly diverse Anopheles mosquitoes, with implications for malaria vector control

Abstract: DNA sequences that are exactly conserved over long evolutionary time scales have been observed in a variety of taxa. Such sequences are likely under strong functional constraint and they have been useful in the field of comparative genomics for identifying genome regions with regulatory function. A potential new application for these ultra-conserved elements has emerged in the development of gene drives to control mosquito populations. Many gene drives work by recognising and inserting at a specific target seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…A recent analysis of ultra-conserved elements (UCEs) from 21 different Anopheles species and search of functional annotations of genes containing UCEs by O'Loughlin et al [12] identified ultra-conserved targets potentially affecting female fertility or lethal recessive phenotype that could be suitable targets for vector control. Amongst the list of potential targets, the AGAP029113 gene is of interest as it contains multiple ultra-conserved sites with a total of 140 invariant sites.…”
Section: Agap029113 Is a Haplosufficient Essential Gene In Anopheles Gambiaementioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of ultra-conserved elements (UCEs) from 21 different Anopheles species and search of functional annotations of genes containing UCEs by O'Loughlin et al [12] identified ultra-conserved targets potentially affecting female fertility or lethal recessive phenotype that could be suitable targets for vector control. Amongst the list of potential targets, the AGAP029113 gene is of interest as it contains multiple ultra-conserved sites with a total of 140 invariant sites.…”
Section: Agap029113 Is a Haplosufficient Essential Gene In Anopheles Gambiaementioning
confidence: 99%
“…Our ability to identify novel genes containing gene drive targets that show high functional constraint has been greatly enhanced by genome resequencing efforts that have covered species across the Anopheles genus, spanning over 100 million years on an evolutionary timescale, as well as wild caught individuals of the closely related Anopheles gambiae and Anopheles coluzzii species [9][10][11]. A recent analysis of genomic data from 21 Anopheles species revealed over 8000 ultra-conserved sites (100% identity) of sufficient length (18bp; corresponding to the minimal sequence recognised by a guide RNA) to be targetable by homing-based gene drives [12]. It is to be expected that among this set of sequences there will be variation in their tolerance for changes to their underlying biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are examining several different and potentially complementary approaches to delay the appearance of resistance, including: aiming to disrupt multiple female fertility genes and/or multiple sequences within the same gene, utilizing promoters that bias toward homologous DNA repair and thus reduce the opportunity for mutation; and, aiming to disrupt genes that are highly conserved in the target mosquito species and/or cannot tolerate changes in their sequence without causing severe harm to the mosquito that would make a mutation less likely to be inherited (for review, see [72]). Methods are being developed to evaluate candidate gene drive targets for their resilience to resistance (e.g., [83][84][85]). For example, cage trials of a gene drive targeting doublesex described above found complete population suppression in A. gambiae mosquitoes with no evidence of resistance, presumably due to functional constraints in the target sequence.…”
Section: Challenges For Implementation Of Genetic Biocontrolmentioning
confidence: 99%
“…The increasing genomic resources available have allowed conservation analysis to be performed across the Anopheles species complex to identify regions that are highly conserved ( Kranjc et al, 2021 ; O’Loughlin et al, 2021 ). The use of these bioinformatic resources can help guide where to target a gene drive, such that it is at a genomic site that could prove intolerant of mutations.…”
Section: Lessons Learnt Towards the Next Generation Of Gene Drivesmentioning
confidence: 99%